Load Frequency Control of Two Area Interconnected Power System Using Fuzzy Logic Control and PID Controller - Tur, Mehmet Rida; Wadi, Mohammed; Shobole, Abdulfetah; Ay, Selim (IEEE, 2018)
Demand for electricity is constantly increasing day by day. The biggest challenge is to provide uninterrupted and high-quality electricity to customers in variable conditions. To accomplish this, the two parameters must always be checked for each condition; these parameters are load distribution and network frequency. In this study, fuzzy logic and Proportional Integral Derivative controller method is applied in power system connected with two different fields to remove the fluctuations of electric energy. For this, MATLAB offers simulation applications and models in Simulink. Both different control directions are compared according to the results obtained. To emphasize the effectiveness of the proposed fuzzy control system, two field-connected power systems were simulated in four scenarios in a wide range of operating conditions. In addition to all these, the performance of the proposed method is compared with a Proportional Integral Derivative tester with simulation studies and the results show the effectiveness and superiority of the proposed approach.
Keywords: fuzzy systems; frequency control; matlab; power system control; proportional control; AUTOMATIC-GENERATION CONTROL; Science & Technology - Other Topics; Energy & Fuels; Engineering